Uganda : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2017)
This paper evaluates the status of fiscal transparency in Uganda, where some key elements of fiscal transparency are in place. These have been augmented in recent years through a number of reforms. The Public Finance Management Act 2015 specifies the budget calendar, the main contents of budget documents, and the roles of the legislature and the executive in the budget process. There are some problems with the coverage, quality, and reliability of some information. Improving fiscal transparency will give the government a better understanding of the fiscal position and its exposure to fiscal risks, which will support effective fiscal and budget management in the face of these challenges.